(3eNJUQ JGQjN GdWHQis - (3eLghds; (3GHf LQjQ GdWHQj , eMeO Hf LQjQ Hf jRjO, CHh LYaQ,J (B310 (3g` s
(3ChdgG (B:s
(3hHYO aEfi deG hbaJ Ydi JGQjN GdWHQi QCjJ eG ajg ef GdJWhjd ai GdTQhM hGdESfGOGJ s
(3GdehLhO efg GdLRA GdChds
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B263 s
Keywords: (3GdJGQjNs